Biodegradation of dispersed oil in seawater is not inhibited by a commercial oil spill dispersant. Issue 2 (April 2018) - Brakstad, Odd G.; Ribicic, Deni; Winkler, Anika; Netzer, Roman
Abstract: Chemical dispersants are well-established as oil spill response tools. Several studies have emphasized their positive effects on oil biodegradation, but recent studies have claimed that dispersants may actually inhibit the oil biodegradation process. In this study, biodegradation of oil dispersions in natural seawater at low temperature (5 °C) was compared, using oil without dispersant, and oil premixed with different concentrations of Slickgone NS, a widely used oil spill dispersant in Europe. Saturates ( n C10- n C36 alkanes), naphthalenes and 2- to 5-ring polycyclic aromatic hydrocarbons (PAH) were biotransformed at comparable rates in all dispersions, both with and without dispersant. Microbial communities differed primarily between samples with or without oil, and they were not significantly affected by increasing dispersant concentrations. Our data therefore showed that a common oil spill dispersant did not inhibit biodegradation of oil at dispersant concentrations relevant for response operations. Graphical abstract: Highlights: The use of an oil spill dispersant did not inhibit oil compound biodegradation. The dispersant did not impact oil-degrading microbial communities. The dispersant will not suppress oil biodegradation at low oil concentrations.